Youth, Agriculture, and Food Security: Understanding the Farmer Regeneration Challenge in Sumatra - Nurarifin, Nurarifin; Kurniawan, Bayu Dwi (Pusbindiklatren Bappenas, 2025)
Agriculture plays a major role in Sumatra’s economy, however, younger generations lack interest in the agriculture sector. This will affect farmer regeneration, thus threatening food security. Currently, comprehensive analyses that reveal the level of farmer regeneration remain scarce. This study seeks to examine the level of farmer regeneration by understanding the determinants of an individual to be a farmer. In addition, we aim to assess the impact of young farmers on food security by utilizing the National Labor Force Survey (Sakernas) from 2018 to 2022. Logistic regression is used to examine how individual characteristics influence the likelihood of being employed as a farmer. The result of the study shows that only a very limited proportion of farmers' descendants in Sumatra choose to carry on their family farming business. Typically, younger individuals, women, individuals with at least a high school degree, and those who attended training, have migrated and adopted digital technology, tend to be more reluctant to become farmers. The analysis also highlights that promoting opportunities for young farmers and lowering the prevalence of undernourishment has a favourable effect on food security. To address the low percentage of younger individuals choosing farming, policies should focus on attracting educated youth through targeted training and incentives. Enhancing digital access and modernizing agriculture can also improve productivity and food security by reducing undernourishment.